Teachers' persuasion to modify health behaviors among students of Bagmati Province, Nepal - Aryal, Bhagwan; Maharjan, Ram Krishna (Journal of Health Promotion, 2021)
Teachers encounter many of the unhealthier behaviors of students that need their support in improving such behaviors. Teachers employ various techniques including instruction, persuasion, and demonstration. They are role models to their students because they present opportunities for observational learning. Teachers can consciously attempt to influence students to change through persuasion. This cross-sectional descriptive survey of 344 teachers in 46 secondary schools aimed to identify the type of health degrading behaviors of the students modified by the teachers and the actions taken in modifying such behaviors, particularly including health persuasion. Teachers were found to involve in the act of persuasion, however, their action was mostly moving around the 'instruction' and 'advise' as the tools for modifying the student's health deteriorating behaviors. More effective persuasive techniques such as demonstrating healthy behaviors by the teachers are necessary to bring evident change.